Effects of cerebral collateral (DSA cerebral angiogram) on clinical presentation and neurological improvement in ischaemic stroke - Mohamed Sabri, Hani Sarah; Bahari, Norafida; Md Nuh, Mohd Syafeeq; Muda, Ahmad Sobri (Longe Medikal, 2024)
DSA (digital subtraction angiography) remains the gold standard in assessing the status of cerebral collaterals. Several studies have shown that the presence of good collateral circulation in ischemic stroke patients is associated with better functional outcomes with reduction of morbidity and mortality. Therefore, in this study, we aimed to assess the correlation between the collateral status seen on DSA cerebral angiogram with the clinical presentation of stroke and patients' functional outcomes. Method: We recruited a cohort of ischemic stroke patients who underwent DSA and collected demographic data, stroke risk factors and clinical data, which includes the National Institutes of Health Stroke Scale (NIHSS) scores, at time of admission. We assessed the collateral status and its grading using DSA and categorized based on established criteria. Subsequently we followed up the patients up at 3 months post stroke event to assess their functional outcomes using the modified Rankin Scale (mRS). Results: There was a significant association between good collateral status and favourable outcome in ischaemic stroke patients (p <0.05). We also found that, there is correlation between the NIHSS (upon discharge) and neurological outcome (MRS at 90 day) with Spearman correlation coefficient of 0.849. Conclusion: In conclusion, cerebral collateral status has the ability to prognosticate the functional outcome of ischemic stroke patients.